ANALISIS PELAKSANAAN PEMBELAJARAN TEMATIK BERORIETASI MULTIPLE INTELLIGENCES DI KELAS AWAL SD MUHAMMADIYAH 9 MALANG - Amelia, Delora Jantung (Universitas Nusantara PGRI Kediri, 2017)
At the age of elementary school children still view an object into a unified whole (Holistic). Along with the development of the era that began to enter the curriculum of 2013 in which the learning has been centered on thematic learning. In thematic learning process is very concerned about the level of thinking of students who still look at something is one part intact. The purpose of this research can be formulated as follows: Knowing the implementation of thematic learning oriented to Multiple Intelligences in elementary school Muhammadiyah 9 Malang, describe the constraints experienced by teachers in implementing thematic learning oriented to Multiple Intelligences in elementary school Muhammadiyah 9 Malang, and describe the way teachers overcome the constraints of implementation Thematic learning oriented to Multiple Intelligences at elementary school Muhammadiyah 9 Malang. The research method used include (1) design, (2) research type, (3) implementation of research, (4) research instrument, (5) data analysis. Descriptive research is one type of qualitative research, namely research based on natural data in the form of words in describing the object under study through the activities of collecting data from a natural setting. Data collection in this research is done by observation, interview and documentation. To collect the data, this research uses the instrument in the form of observation sheet of teacher and student, interview guide. Data analysis is done descriptively both qualitatively and quantitatively. In the linguistic intelligence of teachers in elementary school Muhammadiyah 9 Malang is more likely to facilitate students with writing, discussing, sitting in groups. In the logical math intelligence of the average teacher of the initial class by asking students to come forward with a concrete object. The visual-spatial intelligence of teachers develops them using images, poster images and audio visuals, while for improving kinesthetic intelligence by inviting learners to pat, hand movements or experiment with foot activities. In musical intelligence teachers tend to use memorizing short letters tilawati songs. In the development of interpersonal intelligence teachers more often ask students who are more able or understand to help their friends who can not. Development of intrapersonal intelligence with teachers allows students to learn on their own. In the naturalist intelligence teachers are more likely to tell the activities associated with nature. Constraints faced by teachers while implementing thematic learning oriented to Multiple Intelligences are difficult teachers to develop eight intelligences at a time. How to overcome the obstacles in thematic learning oriented to Multiple Intelligences that is by solving the materials in accordance with the level of Multiple Intelligences. Keywords: Learning Tematics, Multiple Intelligences